AKIBAT HUKUM PEMBATALAN HIBAH TERHADAP KEDUDUKAN SERTIFIKAT HASIL PERALIHAN (Studi Kasus Perkara No. 45/Pdt.G/2023/PN Yyk) - Monica Belinda Oksavina; Naufita Salma Febriana (PSHPM Untag Semarang, 2025)
Grants are in principle irrevocable, but there are certain conditions that allow grants to be canceled. If the conditions of the grant are not met by the grantee, the grantor has the right to withdraw the property that has been donated in accordance with the initial agreement. This study aims to find out whether the decision to cancel the grant at the Yogyakarta State Service number 45/Pdr.G/2023/PN Yyk regarding the cancellation of the grant is in accordance with the applicable legal provisions or not, and to find out the legal consequences of the cancellation of the grant on the certificate of transfer results. Where the legal consequences also have a legal impact on the parties involved. The research method used is Normative Juridical with analytical descriptive research specifications. The type of data used is secondary data. The data collection technique used is library study, then using qualitative data analysis. Based on this research, the results were obtained: First, Decision Number 45/Pdt.G/2023/PN Yyk regarding the cancellation of grants has been in accordance with the applicable legal provisions. Second, the legal consequences of the cancellation of grants to the status of the transitional certificate, namely the return of property that has been donated in the form of land and buildings to the grantor along with his rights. This legal writing is expected to help and provide input and additional knowledge for the parties regarding the issues being researched and are useful for parties interested in the same issue.